Magnetic toner materials containing quaternary ammonium polymers as charge control agents - POLLET; JEAN-CLAUDE (1980)
Magnetic toners containing quaternary ammonium polymers, methods of their formation and utilization of such toners in various electrophotographic imaging systems are disclosed. Toners containing such compounds are suitable for use in inductive development from a biased magnetic toner brush to an electrostatic image, and further subsequently such images may be transferred preferably by electrostatic type methods to a substrate such as plain bond paper.